PHILOSOPHICAL AND IDEOLOGICAL DETERMINANTS OF POSTMODERNISM - Marina Teuvezhevna Aslanova (Вестник Северо-Кавказского федерального университета, 2022)
The postmodernism phenomenon as a phenomenon of public consciousness and the methodological basis research of social reality is considered from philosophical positions. It is shown that the postmodernism turns into the paradigmalny principle of knowledge, gets into consciousness of the person, determines an originality of its mentality and behavior and forms a point counting where all movements of art, social, cultural life of an era are closed.